Isolation and Molecular Identification of Endophytic Bacteria From Rambutan Fruits (Nephelium lappaceum L.) Cultivar Binjai - Suhandono, Sony; Kusumawardhani, Meirina Kartika; Aditiawati, Pingkan (Bogor Agricultural University, Indonesia, 2016)
Interactions between plants and endophytic bacteria are mutualistic. Plant provides nutrient for bacteria, and bacteria will protect the plant from pathogen, help the phytohormone synthesis and nitrogen fixation, and also increase absorption of minerals. These bacteria called plant growth-promoting bacteria. The aim for this study is to identify endophytic bacteria on rambutan (Nephelium lappaceum L.) cultivar Binjai with 16S rRNA. Sequencing results showed that the bacteria is derived from genus Corynebacterium, Bacillus, Chryseobacterium, Staphylococcus and Curtobacterium,which suspected play a role as plant growth-promoting bacteria.